2016
DOI: 10.1007/s00408-016-9954-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Node-Spreading Pattern in Surgically Treated Small-Cell Lung Cancer: A Multicentric Analysis

Abstract: In selected surgically treated SCLC, the long-term survival may be stratified according to the node-spreading pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
2
5
1
Order By: Relevance
“…The male had worse survival than the female, which was consistent with the studies of Wang et al and Xiao et al [20,21]. Lymph nodes metastatic ratio, as a new meaningful indicator for OS of SCLC, was also recognized as an independent predictor [22,25]. The ones with lymph nodes resection performed had better survival than who not, which suggested to conduct lymphadenectomy for resectable SCLC.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The male had worse survival than the female, which was consistent with the studies of Wang et al and Xiao et al [20,21]. Lymph nodes metastatic ratio, as a new meaningful indicator for OS of SCLC, was also recognized as an independent predictor [22,25]. The ones with lymph nodes resection performed had better survival than who not, which suggested to conduct lymphadenectomy for resectable SCLC.…”
Section: Discussionsupporting
confidence: 86%
“…By COX regression analyses, we identified age, sex, T stage, N stage, LNR, surgery and chemotherapy as independent predictors of overall survival. Some of these variables have been studied in previous research for their influence on survival of SCLC [12,[23][24][25][26]. Elder patients had worse survival than the younger ones might because degenerative changes in various aspects of organs function and increased prevalence of all types of comorbidities [27].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have reported favorable outcomes for surgery in patients with stage I SCLC 22,23. A growing number of patients with early stage SCLC receive surgical treatment, resulting in a favorable overall median survival of 29–91 months 2427. The present study evaluated the survival outcomes of surgery versus non-surgery in patients with early stage SCLC, finding that surgery resulted in a better LCSS than that of non-surgery.…”
Section: Discussionmentioning
confidence: 84%
“…In resected pN2 NSCLC, several studies have suggested an increased survival for skip metastases [1417]; however, other reports with contradictory findings also exist [7, 18, 19]. In SCLC, Leuzzi et al [20] found N0 N2-patients showed a worse cancer-specific survival compared to patients with combined N1 N2-involvement (N0 N2 [8 months] versus N1 N2 [22 months]; p = 0.04). Our data showed no statistically significant difference in survival between patients with skip and non-skip N2 metastases.…”
Section: Discussionmentioning
confidence: 99%